Culture-Based Teaching and Learning: Integrating Sasak Culture in English Language Teaching and Learning - Nur Alfilail; Lela Rahmawati; Hilda Hastuti; Ni Ketut Putri Nila Sudewi; Dedi Aprianto (Universitas Mataram, 2026)
Culture is one influential issue that still becomes an important aspect to be studied especially related to education. At the previous time, many English material sources used Western culture which is unfamiliar to students as the source of learning material. Since this material is irrelevant to Indonesian students’ background, many researchers attempted to identify the integration of Indonesian culture on English language teaching. Many of the studies showed positive result on this issue. Since these studies mostly focused on Indonesian culture in general, this present study focuses on identifying the impact of Sasak culture integration on English language teaching. This study is literature review study. This study applied systematic review in analyzing the data. The result of his study shows positive result on the integration of Sasak culture in English language teaching.